Teaching-learning strategy in the Administration course at the Maranhense Center College - FCMA: focus on emotional intelligence - Mota de Sousa, Eliana Viterbia (Salud, Ciencia y Tecnología - Serie de Conferencias, 2023)
To address the longing of the Federal Constitution of Brazil of 1988, on December 22, 2017, Brazil gains a Common National Curricular Base, articulated with other countries through World Organizations. This Base seeks to adjust education throughout the country and levels some rights and objectives such as: knowledge, skills, attitudes, and values, which, when mobilized, are fundamental to solve complex demands of daily life, full exercise of citizenship and the world of work, aiming thus at an education integrated with the whole human being, with its complexity and subjectivity. Therefore, this article seeks to emphasize the importance of emotional competence in the teaching of Administration courses at the FCMA College of Maranhense Center, in order to prepare the student for the world of work and is almost exclusively oriented to identify it as indispensable for the training of successful professionals in the management area. In a secondary vein, the teaching-learning strategies by which emotional intelligence competencies are developed lack further analytical depth, especially with regard to the complexity of higher education contexts in Brazil, since the Common National Curricular Base is specific to basic education, and the scope of the variables that the theme assumes at the theoretical and practical level. Therefore, this article unfolds in problematizing, starting from the Administration course, in FCMA, the construction and application of a teaching-learning strategy for the development of emotional competence, facing questions that are fundamental to the success of the objective: How is such competence taught and what is it used for? What teachers and strategies are used to achieve the purposes of the emotional paradigm in Administration? What capacities are observed in students equipped with subjective emotional skills? How to measure this training in attributes related to intelligibility in the curricular and evaluative plan?